2019
DOI: 10.1108/ijesm-02-2018-0010
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive methodology for setting up rural electrifications with minimum budgets on indigenous villages in Malaysia

Abstract: Purpose This paper aims to propose a comprehensive methodology for setting up rural electrifications for indigenous villages with minimum budgets and the lowest possible cost of electricity (COE). The electricity accessibility of rural area in Malaysia is not fully covered and the cost of extending the grid to these areas can be high as RM 2.7m per km. Lack of vigorous policies and economic attraction of the rural areas are also the main barriers to rural electrification. Electricity is an essential element of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 36 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…The results showed that net income and capital return were 8538 $/year and 13 years, respectively. Soon et al (2019), using HOMER software, conducted a comprehensive survey on providing electricity for a native Malaysian village. Both Load following and Cycle charging scenarios for the batteries were performed to find the lowest cost of electricity and the diesel generator-only system was selected as the criteria for comparison.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that net income and capital return were 8538 $/year and 13 years, respectively. Soon et al (2019), using HOMER software, conducted a comprehensive survey on providing electricity for a native Malaysian village. Both Load following and Cycle charging scenarios for the batteries were performed to find the lowest cost of electricity and the diesel generator-only system was selected as the criteria for comparison.…”
Section: Introductionmentioning
confidence: 99%